DIGITALIZATION OF ADMINISTRATIVE SERVICES: LEGISLATIVE AND THEORETICAL ASPECTS OF ITS IMPLEMENTATION - KRYMCHAK, Liudmyla; VIKHTIUK, Lesya; RUDNICHENKO, Yevhenii (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to analysis of definitions of such concepts as "administrative service", "public service" and "electronic service", which are available in scientific sources. It was determined that the digitalization of electronic services provides significant advantages both for users of these services and for their providers. Among such advantages are: simplification of procedures for interaction of citizens and organizations with bodies that provide administrative and public services, increasing the efficiency of the work of public administration bodies, reducing corruption risks, increasing the efficiency of budget expenditures, obtaining documents from state registers online. The consolidation of these concepts at the legislative level has been studied. The main legal acts that regulate relations in the field of administrative services have been determined. The article describes the advantages of electronic administrative services. An overview of the Unified state web portal of electronic services "Portal Diya" was carried out and an analysis of the main services available on the web portal and in the Diya mobile application was carried out. It was determined that the following services are currently available in the Diya mobile application: driver’s license, vehicle registration certificate, information on car insurance policy, foreign passport, passport of a citizen of Ukraine in the form of a card, tax payer’s card, child’s birth certificate, student card, there is also available payment of fines for violations of the Traffic Rules and payment of debts due to executive proceedings and many others. The article provides examples of citizens’ appeals to state administration bodies through web portals. It was determined that the issues of efficiency of information exchange between state administration bodies and local self-government bodies, integration of their information systems and electronic document management systems, modernization of the information infrastructure of public administration bodies require today significant attention.